Validation of the abrasion resistance test protocols and performance criteria of EN13595: The probability of soft tissue injury to motorcycle riders by abrasion resistance of their clothing. (June 2017) - Meredith, Lauren; Hurren, Christopher; Clarke, Elizabeth; Fitzharris, Michael; Baldock, Matthew; de Rome, Liz; Olivier, Jake; Brown, Julie
Abstract: Introduction: Motorcyclists represent an increasing proportion of road users globally and are increasingly represented in crash statistics. Soft tissue injuries are the most common type of injuries to crashed motorcyclists. These injuries can be prevented through the use of protective clothing designed for motorcycle use. However, the quality of such clothing is not controlled in many countries around the world. A European Standard was developed to assess the performance of clothing but as this is not mandatory, clothing certified to this Standard is difficult to obtain. Given the importance of this Standard, and that it has been validated only once, further validation work is required. Methods: In-depth crash investigation data were used to investigate the relationship between the abrasion resistance performance of clothing and real-world injury outcome. Clothing was collected from riders who crashed on public roads in Sydney and Newcastle, Australia. This clothing was tested according to the EU Standard and the time to hole was recorded. Hospital medical records were reviewed and the association between a rider suffering a soft tissue injury and the time-to-hole for the garment was examined. Results: The probability of soft tissue injury for Level 1 Standard garments was between 40–60%, but more than 60% of garments tested failed to meet the minimum requirement. Conclusions: The findings of this study provide qualified support for the Standard, with a marginal association between time-to-hole and injury being found. Practical Implications: This work supports the need for improved safety performance and an increased number of high performing garments being available to motorcyclists. Highlights: The Cambridge Abrasion Resistance Method is appropriate to assess motorcycle clothing. Current EN13595:2002 Level 2 criteria are associated with a low (19%) probability of injury. Level 1 criteria are associated with between 40 and 53% probability of injury. Over 60% of garments in this Australian sample failed to meet minimum requirements.